Bringing the margin to the focus: 10 challenges for riparian vegetation science and management. (28th July 2022) - Rodríguez‐González, Patricia M.; Abraham, Eleni; Aguiar, Francisca; Andreoli, Andrea; Baležentienė, Ligita; Berisha, Naim; Bernez, Ivan; Bruen, Michael; Bruno, Daniel; Camporeale, Carlo; Čarni, Andraž; Chilikova‐Lubomirova, Mila; et al.
Abstract: Riparian zones are the paragon of transitional ecosystems, providing critical habitat and ecosystem services that are especially threatened by global change. Following consultation with experts, 10 key challenges were identified to be addressed for riparian vegetation science and management improvement: (1) Create a distinct scientific community by establishing stronger bridges between disciplines; (2) Make riparian vegetation more visible and appreciated in society and policies; (3) Improve knowledge regarding biodiversity—ecosystem functioning links; (4) Manage spatial scale and context‐based issues; (5) Improve knowledge on social dimensions of riparian vegetation; (6) Anticipate responses to emergent issues and future trajectories; (7) Enhance tools to quantify and prioritize ecosystem services; (8) Improve numerical modeling and simulation tools; (9) Calibrate methods and increase data availability for better indicators and monitoring practices and transferability; and (10) Undertake scientific validation of best management practices. These challenges are discussed and critiqued here, to guide future research into riparian vegetation. This article is categorized under: Water and Life > Nature of Freshwater Ecosystems Water and Life > Stresses and Pressures on Ecosystems Water and Life > Conservation, Management, and Awareness Abstract : Ten challenges to enhance riparian vegetation science and management.